VD_FINDINFO HC / 2015 / 234 vom 16. Februar 2015 - VD Tribunal cantonal (2015)
CONTRAT DE TRAVAIL, FIDÉLITÉ, ACTIVITÉ ACCESSOIRE, RÉSILIATION | 321a al. 3 CO, 329d al. 3 CO, 337c al. 2 CO, 319 let. a CPC (CH)